2012
DOI: 10.1049/iet-com.2011.0808
|View full text |Cite
|
Sign up to set email alerts
|

Energy efficient coordinated radio resource management: a two player sequential game modelling for the long-term evolution downlink

Abstract: Inter-cell interference (ICI) is a key limiting factor to the radio frequency (RF) energy performance of a multi-cell multi-user radio access network (RAN). The channel quality of the cell edge users is greatly impaired by ICI owing to the fact that cell edge users are furthest away from their serving base stations (BSs) and closest to the interfering BSs. Consequently the BS is compelled to allocate more physical resource blocks [PRBs (In LTE a PRB spans 12 sub-carriers each with a bandwidth of 15 kHz over a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 21 publications
0
18
0
Order By: Relevance
“…Fig. 5 shows the simulation results of peak cell capacity versus normalized cell traffic load for a variety of static and dynamic interference mitigation schemes [13], [14]. The baseline is a hard frequency reuse 1 (HFR1) scheme, which shows a peak capacity of 58 Mbps/cell when the cells are unloaded (i.e., minimum inter-cell interference).…”
Section: B Simulation Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Fig. 5 shows the simulation results of peak cell capacity versus normalized cell traffic load for a variety of static and dynamic interference mitigation schemes [13], [14]. The baseline is a hard frequency reuse 1 (HFR1) scheme, which shows a peak capacity of 58 Mbps/cell when the cells are unloaded (i.e., minimum inter-cell interference).…”
Section: B Simulation Resultsmentioning
confidence: 99%
“…The disadvantage with a TDD-based coordinated interference avoidance scheme is the need for two prerequisites [14]: (1)…”
Section: Discussion and Challengesmentioning
confidence: 99%
See 1 more Smart Citation
“…5 show an implementation of the proposed interference avoidance scheme, in comparison with a baseline hard frequency reuse 1 setup, and a Sequential Game Coordinated (SGC) interference avoidance scheme [7]. The simulation parameters can be found in Table I. 1) Low Traffc Regime: At a low cell activity level, which corresponds to a low traffic load in the area, the overall interference power received at any point is low.…”
Section: Interference Avoidance Resultsmentioning
confidence: 99%
“…We will primarily focus on the scheduling techniques used to avoid interference between cofrequency transmitters. It has been demonstrated that interference avoidance can be partially and completely achieved through coordinated scheduling techniques between transmitter pairs on a dynamic level using either pre-set or learning algorithms [13], [14]. This has a similar philosophy and performance to hard-or soft-frequency-reuse (SFR) schemes [15].…”
Section: Review: Interference Managementmentioning
confidence: 99%